The Mass Media News Framing Analysis of Polemic of Regulations on Prevention and Handling Sexual Violence in Higher Education - Ratih Anbarini; Adry Alim Priyatna; Annisa Nursalsabillah; Marlia Marlia (Universitas Muhammadiyah Ponorogo, 2023)
Regulation of the Minister of Education, Culture, Research, and Technology (Permendikbudristek) Number 30 of 2021 concerning the Prevention and Handling of Sexual Violence (Pencegahan dan Penanganan Kekerasan Seksual/PPKS) in Higher Education, which was signed in August 2021, raises pros and cons in society. The phrase